New methodology to optimize sorting in wood drying - D. M. Elustondo; L. Oliveira; S. Avramidis (Maderas: Ciencia y Tecnología, 2014)
One important problem in lumber drying is to maintain the lumber moisture content distribution within certain minimum and maximum values. Over-drying and under-drying are common causes for lower grade recovery and dimensional stability problems. It is known that both over-drying and underdrying can be reduced by sorting green lumber into different moisture content groups and sorting also offers the opportunity to redesign drying schedules. In this study, a new methodology was designed and tested to optimize kiln drying of lumber by implementing green sorting coupled with modified drying schedules. The methodology was applied to optimize the drying of 114 by 114mm2 hem-fir lumber sorted with an NMI capacitance type meter at a local sawmill. It was found that in comparison to unsorted lumber, sorting into three groups can reduce the drying time by 7% approximately and recover around 3/4 of the under-dried lumber. The experimental data on lumber degrade and moisture gradients measured after drying were also reported in this paper.